An analysis of the cultural characteristics of the emerging black tourist market in Vanderbijlpark - Taylor, Tish Frances (My University, 2013)
In recent years there has been a considerable interest in the cultural aspect of tourism (Reisinger & Turner 2003:1 ). Culture in its various forms and dimensions has a significant impact on tourism planning and development, management and marketing. Unfortunately literature that examines the impact of culture on tourism concentrates mostly on expressions of material forms of culture such as the arts, music, architecture or crafts. Research regarding the variables of national cultures such as values, perceptions, rules of behaviour and satisfaction has been neglected. The importance of cultural variables for tourist holiday experiences is important and affects satisfaction and consequently repeat visitation. Thus the cultural variables which influence the quality of the interpersonal interaction between tourists and hosts, can significantly add to tourist holiday experiences and satisfaction. The past few years has witnessed a dramatic change in the composition and nature of domestic tourism in South Africa (Futter & Wood 1997:1 ). Black tourists are emerging as the largest travelling group within South Africa and it is important to the tourism industry that cultural variables of this group be examined. Tourism has experienced a growing internationalization and considerable attention has been paid to the issue of cultural diversity as a result of this growth in international travel. Tourism is a service industry where people from all nationalities meet and the crossing of different cultures takes place. This cross-cultural interaction leads to socio-cultural impacts which affect both the tourist and the host community. By understanding the cultural characteristics of various travelling groups to and around South Africa, socio cultural impacts will be minimised and the benefits of tourism can be appreciated. The target group for this study was black tourists to Vanderbijlpark. This is a large domestic tourism group and understanding the cultural characteristics of this group will enable the tourism industry to better plan, develop and market specific tourism packages. Research for this study was undertaken at a jazz festival in Vereeniging. Field workers randomly interviewed respondents using a questionnaire. The questionnaire consisted of five sections, namely demographic particulars, personal values, rules of behaviour, perceptions and satisfaction. The data was analysed to provide information regarding the cultural characteristics of the black tourism market in Vanderbijlpark. Respondents were categorised using the demographic data, the culture sections of the questionnaire were analysed in order to give descriptive results of each of the cultural variables. Each variable was analysed to determine its importance to respondents, thus categorising respondents according to their cultural characteristics. A factor analysis was completed in order to synthesise the large amount of data and for each cultural variable smaller, more descriptive factors were identified and used to describe the black tourism market in Vanderbijlpark.
Thesis (B. Tech. (Tourism management))--Vaal University of Technology.
Keywords: Tourism; Cultural differences; Black tourists; 338.47910968223; Tourism -- South Africa